REDD+ Financing to Enhance Climate Change Mitigation and Adaptation and Biodiversity Co-benefits: Lessons from the Global Environment Facility - Kanako Morita; Ken'ichi Matsumoto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
This study explores ways to effectively and efficiently finance Reducing Emissions from Deforestation and Forest Degradation (REDD+) activities to enhance climate change adaptation and biodiversity conservation by drawing on lessons from the Global Environment Facility (GEF). The study analyzed trends in the focal areas of GEF forest-related projects, the executing and implementing agencies involved in GEF forest-related multi-focal area projects, and the cofundraisers’ trends in GEF forest-related multi-focal area projects. The analysis of GEF forest-related projects identified ways to finance REDD+ mobilization and distribution to enhance its multiple benefits. The key agencies that support REDD+ activities and enhance these co-benefits are the United Nations Development Program (UNDP), the Food and Agricultural Organization (FAO), the World Bank, the United Nations Environment Program (UNEP), and the national governments of developing countries. GEF and the co-fundraisers—multilateral aid agencies, such as UNDP, the World Bank, FAO, the Asian Development Bank, and UNEP, bilateral aid agencies, such as Germany, the United States and the European Union, the private sector and nongovernmental organizations—all work to enhance REDD+ co-benefits. Because private contributions to the GEF are limited, it is important to design a scheme to mobilize more private financing for REDD+.